Study of photoreactivation in microbiological crops obtained from microbial loading of the surface of strawberries subject to different doses of short-wave UV-C ultraviolet light - Lara Oviedo, Gustavo Andres; Navarro, Maria Camila; Altamiranda, Jean Atencio (Revista Colombiana de Investigaciones Agroindustriales, 2018)
Currently the government agency US FDA (Food and Drug Administration) has approved the use of (UV-C) ultraviolet short-wavelength light disinfection of fruit, because exposure to ultraviolet light can reduce load of pathogenic microorganisms that may contain on their surface and thus extend the life of products favoring producers. However, misuse of ultraviolet light may also have risks developing resistance of microorganisms to UV-C through a process known as photoreactivation. Objective: To determine the degree of photoreactivation in microbiological cultures that have undergone different doses of ultra violet light short-wave UV-C. Materials and methods: samples of common strawberries to which different doses of UV-C were applied including conventional were taken. the antibiotic effect of UV-C on the surface of the strawberries was analyzed by pre-culture - post. Results and conclusions: the sample under the distance currently used by industry (30 cm from the UVC source for 7.5 min) proved effective distance for decrease microbial growth. However, at a high dose (20 cm from the source and 7.5 min) cultures of coliform bacteria and yeasts showed an exponential microbial growth compared to the other samples (test performed in duplicate), which proves the antithesis of theory that the higher was the dose of UV-C rays would be greater DNA damage by inhibiting microorganism’s growth giving strength to the theory the higher the dose, the greater stimulus photoreactivation and UV-C resistance.